2002
DOI: 10.1073/pnas.132142799
|View full text |Cite
|
Sign up to set email alerts
|

All intermediates of the arsenate reductase mechanism, including an intramolecular dynamic disulfide cascade

Abstract: The mechanism of pI258 arsenate reductase (ArsC) catalyzed arsenate reduction, involving its P-loop structural motif and three redox active cysteines, has been unraveled. All essential intermediates are visualized with x-ray crystallography, and NMR is used to map dynamic regions in a key disulfide intermediate. Steadystate kinetics of ArsC mutants gives a view of the crucial residues for catalysis. ArsC combines a phosphatase-like nucleophilic displacement reaction with a unique intramolecular disulfide bond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
131
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(137 citation statements)
references
References 40 publications
4
131
0
2
Order By: Relevance
“…The reversible conformational transitions monitored by two-dimensional NMR spectroscopy along with the catalytic reaction provide insights into the mechanism of arsenate reduction. A similar result regarding the conformational switch in S. aureus ArsC was reported previously (18).…”
Section: Characteristics Of the Reduced And Oxidized Forms Of B Subtsupporting
confidence: 90%
See 2 more Smart Citations
“…The reversible conformational transitions monitored by two-dimensional NMR spectroscopy along with the catalytic reaction provide insights into the mechanism of arsenate reduction. A similar result regarding the conformational switch in S. aureus ArsC was reported previously (18).…”
Section: Characteristics Of the Reduced And Oxidized Forms Of B Subtsupporting
confidence: 90%
“…between them are 1.38 and 1.51 Å for 130 pairs of C ␣ atoms determined using DALI (39). The conservation of the P-loop and the three essential cysteine residues (Cys 10 , Cys 82 , and Cys 89 ) suggests that they may share a similar catalytic mechanism of arsenate reduction (18,22). A previous study demonstrated that the arsenate reduction activity of S. aureus ArsC takes place via a triple disulfide cascade involving three cysteines (Cys 10 , Cys 82 , and Cys 89 ) (18).…”
Section: Solution Structures Of the Reduced And Oxidized Forms Of B mentioning
confidence: 95%
See 1 more Smart Citation
“…The structure of the ArsA component of the ATP-dependent extrusion pump ArsAB with antimonite bound in close proximity to the nucleotide-binding site was able to provide some insight into the active transport of As(III) out of the cell (2). Additionally, structural characterization of substrate and product complexes of the arsenate reductase ArsC, which reduces arsenate (AsO 4 3Ϫ ) to arsenite (AsO 2 Ϫ ), has helped elucidate this step of the arsenic detoxification pathway (3,4). Recent studies of E. coli ArsD indicate that it is a metallochaperone, transporting As(III) to ArsA for extrusion (5).…”
mentioning
confidence: 99%
“…Previously, we have shown that the three-stranded coiled coil TRI peptides [Ac-G(L a K b A c L d E e E f K g ) 4 G-NH 2 ] designed with the heptad repeat strategy, such as TRI L16C (sequences of all peptides are in Table 1), were able to model the unusual trigonal thiolate Hg(II) coordination geometry seen in the MerR metalloregulatory protein (7). We have also examined the binding of the heavy metals Cd(II), Pb(II), and Bi(III) to the TRI peptides to better understand their modes of toxicity (8,9).…”
mentioning
confidence: 99%